Kdy je třeba říci dost: Když etická dilemata ve feministickém výzkumu překročí určitou mez - Marie Dlouhá (AntropoWebzin, 2014)
Every researcher has to deal with numerous ethical questions during the whole research process. Ethical dilemmas are partially based on the theoretical perspective of the researcher. My perspective in gender and entrepreneurship research was a feminist approach, which is primarily based on rejecting the valuefree nature of research, and accepting a political commitment to create knowledge which could improve the position of women in society. This article presents research which started in autumn 2012. I planned to do a complex case study of one project which helps women to start their own businesses. The biggest ethical problem which emerged in the process of research was the imbalance between my values and the values of the organizers and participants of this project. Double responsibility – towards participants of the research and towards my scientific caused the termination of the research. The main reason was the fact that it would be impossible to present and publish any results – any form of presentation would be against the values of one or the other side. The article shows that terminating research is one of the ways a researcher can solve his/her ethical dilemmas.